Fatigue design procedure for welded hollow section joints : IIW Document XIII-1804-99 and IIW Document XV-1035-99 : recommendations of IIW Subcommission XV-E - Zhao, Xiao-Ling; Packer, Jeffrey A. (Woodhead Publishing series in welding and other joining technologies., 2000)
This International Institute of Welding (IIW) report was presented at the 52nd Annual Assembly in Lisbon in June 1999. It contains recommendations representing a consensus on international best practice, focusing on a 'hot spot stress' approach. A wide range of joint types is covered, the new fatigue design curve for both RHS and CHS is dealt with and detailed values for stress concentration factors are provided. The purpose of this current IIW document is to serve both as an International Standards Organisation (ISO) draft specification and as a model standard for national and regional specifications worldwide. The Recommendations (Part one) and Commentary (Part two) were edited by Dr X-L Zhao of Monash University, Australia and Professor J A Packer of the University of Toronto, Canada.